Nilai Ekonomi Total Hutan Mangrove Desa Margasari Kecamatan Labuhan Maringgai Kabupaten Lampung Timur - Ria Indrian Ariftia; Rommy Qurniati; Susni Herwanti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
The utilization of non timber forest products that represent potential mangrove forests lack of consideration of various products and services that can be produced. Conversion of mangrove forest to other uses deemed more profitable than explored the potential. The purpose of research that was conducted in April-May 2013 were to calculate the total economic value of mangrove forest in Margasari village sub district of Labuhan Maringgai district of Lampung Timur. Respondents are 43 mangrove forest communities selected by purposive sampling. Data were collected by direct observation and interviews, the analyzed using the formula total economic value (TEV). The results showed the total economic value of mangrove forests of Rp 10,530,519,419.00 of year consisted by (1) direct use value of Rp 1,877,440,000.00 of year of utilization of fuel wood, leaves and mangrove fruit, (2) indirect use values of Rp 8,915,036,479.00 of year of natural food provider for the marine life, (3) option value of Rp 103,425,000.00 of year of biodiversity and (4) existence value of Rp 1,580,000.00 of year of society's willingness to pay. Keywords: mangrove forest, total economic value, use value, non use value